Early Childhood Health-Protective Behavior Against Environmental Tobacco Smoke Exposure in Households (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2021)
Children who live in agricultural, coastal, and industrial areas are at risk of experiencing diseases due to their exposure to environmental tobacco smoke because a lot of smokers live in these areas. The objective of this study is to determine the differences in health-protective behavior of parents who have children in the geographical residence. The study used a quantitative approach, cross-sectional design, and purposive sampling. There are 175 parents with children under five years who live in coastal, agricultural, and industrial areas in Semarang, Central Java, Indonesia. Data collection was performed using a questionnaire. The dependent variable was the health-protective behavior of parents with children against exposure to cigarette smoke, while the independent variable was the geographical residence. The one-way ANOVA test was used to measure differences in the health-protective behavior of parents living in these areas. The results showed that there was no difference in the parental health-protective behavior in an agricultural, coastal, and industrial region (p=0.091, p>0.05). In conclusion, the respondents exhibit health-protective behavior that dies not fully control exposure to environmental tobacco smoke.